Simulaç\~ao de parceria público-privada para as rodovias federais: Impactos sobre orçamento fiscal, usuários e contribuintes - Fabiano Mezadre Pompermayer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This article presents a simulation of Public-Private Partnership for the maintenance and operation of all paved federal highways. To do so, we evaluate the distribution of benefits and costs between taxpayers, government and road users as a way to set toll values bankable by users, easing the tax burden on all taxpayers with regard to spending on highways. Then, we propose the use of a concession model in which part of the concessionaire's revenue comes from toll collection and part from payment for availability by the government. In addition, the concessionaire must pay the government a grant value per vehicle, so that the total amount of the grant is variable with the demand. Such a mechanism, in addition to reducing the demand risk allocated to the concessionaire, allows cross-subsidization of highways with high traffic volume for the low volume ones. Considering the average costs of operation and maintenance of highways under concession, we evaluate if the collection with the proposed tolls would be sufficient to cover the costs. The results indicate that even considering only the roads not conceded yet, generally low traffic, the fiscal costs of such a model would be smaller than the average expenditures executed by DNIT with maintenance and operation of federal highways. And also ensure higher level of quality, with direct benefits to users and indirect ones to the whole society.
Keywords: H54; H43; O22; 330; concessions; roadways; costs and benefits distribution